THE TEACHING OF SPEAKING SKILL AT SMA ISLAM SABILAL MUHTADIN BANJARMASIN - Iwan Perdana (Vidya Karya, 2013)
This research has four aims to describe: (1) the requirements of English teacher at SMA Islam Sabilal Muhtadin Banjarmasin, (2) the teaching materials used, (3) the media used in teaching, (4) the technique used by english teacher in teaching speaking skill, (5) the assessment carried out by English teacher.The design of the research belongs to descriptive research. The result of the observation, field notes, and interview are : (1) the requirements of English teacher at SMA Islam Sabilal Muhtadin Banjarmasin are good moslem, smart, responsible, polite, and creative,(2) The English teacher prepared everything needed in teaching by making lesson plan based on the syllabus, (3) the English teacher used media to support the process of teaching speaking skill, (4) the English teacher applied some techniques, (5) the English teacher assess the performance of students by watching their pronunciation, grammar and vocabulary.